Pulmonary Hypertension in Obese Mice Is Accompanied by a Reduction in PPAR-γ Expression in Pulmonary Artery - Gonçalves, Any Elisa de Souza Schmidt; Rocha, Guilherme Zweig; Marin, Rodrigo; Camargo, Rafael Ludemann; Santos, Andrey dos; Carmo, Helison do; Guadagnini, Dioze; Petrucci, Orlando; Moysés, Zenaide Providello; Salemi, Vera Maria Cury; Oliveira, Alexandre Gabarra; Saad, Mario José Abdalla (Frontiers in Endocrinology, 2021)
Obesity and insulin resistance (IR) are well-studied risk factors for systemic cardiovascular disease, but their impact on pulmonary hypertension (PH) is not well clarified. This study aims to investigate if diet-induced obesity induces PH, and if peroxisome proliferator–activated receptor (PPARg and/or endoplasmic reticulum (ER) stress are involved in this process. Mice were maintained on a high-fat diet (HFD) for four months and IR and PH were confirmed. In a separate group, after four months of HFD, mice were treated with pioglitazone (PIO) or 4-phenylbutyric acid for the last month. The results demonstrated that HFD for at least four months is able to increase pulmonary artery pressure, which is maintained, and this animal model can be used to investigate the link between IR and PH, without changes in ER stress in the pulmonary artery. There was also a reduction in circulating adiponectin and in perivascular adiponectin expression in the pulmonary artery, associated with a reduction in PPARg expression. Treatment with PIO improved IR and PH, and reversed the lower expression of adiponectin and PPARg in the pulmonary artery, highlighting this drug as potential benefit for this poorly recognized complication of obesity.